In-Silico Optimization of Macrolactin A from Sponge-Associated Bacteria and Its Derivatives as Eco-Friendly Antifoulants - Balansa, Walter; Riyanti; Hinonaung, Jelita Siska Herlina (Jurnal Ilmiah PLATAX, 2025)
Marine biofouling causes significant economic and environmental damage creating an urgent demand for eco-friendly antifoulants. This in silico study aimed to evaluate the antifouling efficacy and ecotoxicological profile of macrolactin A (1), previously isolated from Indonesian sponge-associated Bacillus spp., alongside its computationally generated derivatives (1a-1f, 2a–2k) using Biotransformer 3.0. Molecular docking was utilized to assess binding affinities against key protein targets—the bacterial BAM complex, GSK-3 , and acetylcholinesterase (AChE)—and used EPI Suite™ to predict environmental safety. All tested compounds exhibited robust binding affinities (  kcal/mol) against all targets likely binding to allosteric sites. ANOVA revealed significant differences ( ) in binding strength, with derivatives displaying a distinct preference for GSK-3  over AChE and BAM ( ). However, the broad-spectrum affinity across all three targets supports a potential multi-mechanism mode of action. Crucially, most derivatives showed low toxicity and bioaccumulation potential compared to commercial antifoulants such as Irgarol 1501, SeaNine 211, and Selektope®. Notably, analogues 1a-1c and 2e were predicted to be readily biodegradable. This study identified 1a–1c and 2e as leading candidates for eco-friendly antifoulants and provides a strong basis for future experimental development of novel, sustainable marine coating candidates. Keywords: ecofriendly antifouling; in silico; macrolactin; molecular docking; sponge-associated bacteria